2020
DOI: 10.1021/acscatal.9b05413
|View full text |Cite
|
Sign up to set email alerts
|

Domino C–H Activation/Directing Group Migration/Alkyne Annulation: Unique Selectivity by d6-Cobalt(III) Catalysts

Abstract: Distinct selectivity control in Cp*Co III -catalyzed domino C−H activation/pyridine directing group migration/ alkyne annulation has been accomplished through the nucleophilicity of an organometallic cobalt intermediate with a d 6 electron configuration. Detailed mechanistic studies provided compelling evidence for a facile C−H activation along with a favorable migration of the directing group for the Cp*Co III catalysis, rather than the β-oxygen elimination observed for a (CO) 3 Mn I manifold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 99 publications
0
31
0
Order By: Relevance
“…In a recent example, Ackermann and co-workers reported a selective domino C–H activation, pyridine migration-annulation sequence catalyzed by a pentamethyl cyclopentadienyl (Cp*) Co complex ( Scheme 4 C). 60 Likewise, this reaction could not be accomplished by Rh or Ru, underlining the potential of 3d metals to serve not only as more sustainable alternatives, but in many cases offering contrasting reactivity. Until now, however, undirected Mn and Co examples of this type have been elusive.…”
Section: Next Generation Metal Catalystsmentioning
confidence: 99%
“…In a recent example, Ackermann and co-workers reported a selective domino C–H activation, pyridine migration-annulation sequence catalyzed by a pentamethyl cyclopentadienyl (Cp*) Co complex ( Scheme 4 C). 60 Likewise, this reaction could not be accomplished by Rh or Ru, underlining the potential of 3d metals to serve not only as more sustainable alternatives, but in many cases offering contrasting reactivity. Until now, however, undirected Mn and Co examples of this type have been elusive.…”
Section: Next Generation Metal Catalystsmentioning
confidence: 99%
“…Its parent dibenzo[f,h]quinoline, i.e bzbzqH, reacted more sluggishly affording the annulation product in 34 % yield after 24 h. If these informations plead in favour of a dominant electrophilic C-H bond activation pathway where an auxiliary base such as the heterocyclic substrate itself or any other base could act unbonded to the metal center for instance, the contribution of a concurrent CMD mechanism cannot be ruled out when LiNHAc is present. Worthy to note, in the case of a domino catalysis promoted by Cp*Co(III), Ackermann et al 58 have indeed recently priviledged the socalled base assisted intramolecular electrophilic-type substitution (BIES) mechanism rather than the CMD one even though the formulation of their mechanism is again very similar to that of the CMD where the formation of an agostic intermediate remains crucial. However, this contribution might be minor if one considers that in the absence of AgBF4 the conversion in the conditions required for the CMD mechanism to operate corresponds to the maximum achievable value in the absence of any oxidizing agent with 10 mol% catalyst ( 124 Another example adressed by Qu and Cramer 15 for the C-H bond functionalization with diazo compounds catalyzed by Cp*Co(III)/Rh(III) complexes tends to suggest the possible coexistence of two mechanisms of C-H bond activation.…”
Section: Catalytic Application Of the Amidate Assisted C-h Bond Activmentioning
confidence: 99%
“…49 We now decided to test experimentally the conclusions drawn from the theoretical study of the Ni(II)/Pd(II) model dyad to the CMD mechanism-promoted cyclometallation reaction by focussing our interest on the Cp*Co(III) system, having in scope that a good part of the recent applications of Cp*Co(III) catalysts 17,55,56 to C-H bond functionalization apparently proceed by a different mechanism, i.e via the electrophilic activation 57 of the C-H bond. Recent reports tend indeed to priviledge the electrophilic pathway 58,59 even though in some cases the formal formulation of the mechanism makes the distinction with the CMD 16,60,61 one rather difficult. It is important to mention that known syntheses (scheme 1) of Cp*Co(III)-metallacycles are based on the use of sensitive Cp*Co(I)L2 (L=CO; Me3SiCH=CH2) complexes and rely on an oxidative addition step requiring expensive iodo-arene substrates such as 2-(2-iodophenyl)pyridine (oxidative addition).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the nucleophilic-addition pathway was employed by Ackermann’s group for the synthesis of a variety of indolizinones 58 from N -pyridyl-protected 2-pyridones 56 and bulky propargyl carbonates 57 ( Scheme 22 ). 42 After carrying out DFT and experimental studies to elucidate the reaction mechanism, it was found that intermediate XXVI would be formed after a reversible (and not rate determining) metalation of the aromatic ring, followed by migratory insertion into the triple bond of the corresponding propargyl carbonate 57 . Then, nucleophilic addition of that species to the directing groups would lead to its migration, forming XXVII .…”
Section: Alkynes As Coupling Partners Under Cp*co(iii) Catalysismentioning
confidence: 99%